Insult in National Criminal Law and Islamic Criminal Law: Sanctions Perspective and Legal Developments Review - Desia Rakhma Banjarani; Taufani Yunithia Putri; Almira Novia Zulaikha (Ius Poenale, 2023)
Insulting still very colorful in this life. Nevertheless, honor, dignity and fame for all people must be maintained and protected, and everyone must be safe from all disturbances and all efforts to humiliate based on Islamic provisions and state law. Based on this background, the formulation of the problem that will be discussed in this study is how are the sanction provision of insult in Indonesian law? How is the development of Islamic criminal law regarding criminal acts of insult in Indonesia? The method used in this study is normative research with data sources used in this study based on primary data sources and secondary data sources. The main data source is based on the Law No. 1 of 2023 concerning Criminal Code (KUHP), while secondary data is obtained from related books or articles. Sanctions for criminal acts of insult under Indonesian law are regulated in the Law No. 1 of 2023 concerning Criminal Code, which are grouped into 8 types of actions of insulting and The Electronic Information and Transaction Law or the ITE Law. Whereas in Islamic criminal law, it is regulated in the Al-Qur'an and Hadith Sahih: Muttafaq alaih. Criminal sanctions for insult in the development of Islamic criminal law use takzir punishment or are called jarimah takzir. In the modern era like now Islamic criminal law remains a judge's consideration for criminal imposition according to the provisions of takzir punishment.